2016
DOI: 10.18512/1980-6477/rbms.v15n3p450-460
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Tolerant Maize Genotypes Invest in Root System and Maintain High Harvest Index During Water Stress

Abstract: -Drought is considered the primary limitation to agriculture and, can reduce grain yield by up to 60% when occurs at pre-flowering in maize. In this context this research, aimed to understand the maize genotypes behavior to drought management and carbon partitioning between grain production and structures to maintain hydration when submitted to drought. Maize genotypes tolerant (DKB390 and P30F35) and sensitive (BRS1010 and 2B710) to drought were grown in a greenhouse using two water conditions: irrigated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Regarding gas exchange, one of the first responses of plants to water deficit is the stomatal limitation [25,26], reducing gs and E as an evolutionary mechanism that reduce the loss of water to the atmosphere [27]. Stomatal closure under water deficit conditions reduces CO2 absorption by the plants, reducing carbon in the mesophyll of the leaves, thus reducing the photosynthetic rate and plant development [28,2].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gas exchange, one of the first responses of plants to water deficit is the stomatal limitation [25,26], reducing gs and E as an evolutionary mechanism that reduce the loss of water to the atmosphere [27]. Stomatal closure under water deficit conditions reduces CO2 absorption by the plants, reducing carbon in the mesophyll of the leaves, thus reducing the photosynthetic rate and plant development [28,2].…”
Section: Discussionmentioning
confidence: 99%
“…In one approach, genotypes are more efficient in saving water by fixed carbon, thus maintaining water status (Water Use Efficiency). Alternatively, some genotypes can maintain the water status by escaping from stress (deeper roots, for example), keeping the stomata more open and maintaining photosynthesis, that is, they spend more water (Water Use) (Blum 2009;Avila et al, 2017). The higher gaseous exchanges and water status found in the genotypes evaluated in the present study (mainly DKB 390) show that these plants may have greater tolerance to drought when chitosan is applied, mainly due to the better water use (WU) and not to the greater water use efficiency (WUE).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that maize plants used in this study respond well to moderate water deficit and efficiently use water provided by irrigation, especially in the case of plant biomass and kernels production. During water scarcity, new maize genotypes are capable to balance adequately water use between grain production as plant hydration maintenance [64]. Moreover, [65] observed that even if water shortage is commonly responsible for great maize yield loss, the timing of water deficit can positively affect IWP.…”
Section: Discussionmentioning
confidence: 99%